Bimbingan Teknis Peningkatan Kompetensi Pengawasan Pekerjaan Konstruksi Pembangunan Kampung Nelayan Merah Putih - Ferry Firmawan; Hendra Masvika; Sutik; Purwanto Purwanto; Dhini Rahmahajsuly; Maesa Widiyafi; Cahya Hari Prayoga (Jurnal Pengabdian KOLABORATIF, 2026)
The development of the Kampung Nelayan Merah Putih project in the coastal area of Centra Java faces significant challenges, including land subsidence, tidal flooding, and highly saline environmental conditions that may reduce infrastructure durability. These conditions require competent construction supervision to ensure project quality, schedule, and cost performance. This Community Service Program aimed to enhance the technical and managerial competencies of personnel from the Semarang Fishing Port Center (BBPI) through technical guidance on construction supervision. The program consisted of three stages: dissemination of construction quality management principles, training on field inspection methods and technical administration, and stakeholder coordination to harmonize supervision practices. Program effectiveness was evaluated using pre-test and post-test assessments involving 22 participants who completed 18 questions. The results demonstrated a substantial improvement in participants' knowledge, with the mean score increasing from 59.77 (62.9% of the maximum score) to 81.59 (85.9%), representing a gain of 21.82 points (36.5%). The minimum score increased from 50 to 70, and no participant scored below 70 in the post-test. The training also strengthened participants' shared understanding of quality control, contract administration, field inspection, and the achievement of the project's triple constraints. These findings indicate that the technical guidance effectively improved construction supervision competencies and contributed to more professional, accountable, and sustainable management of coastal infrastructure projects.